Rekonstruksi Kaidah Penulisan Hamzah - Deni Hudaeny; Naira Kamila Hudaini (SUHUF, 2025)
The main focus of this study explains the reconstruction or rearrangement of the writing of hamzah in the Indonesian Standard Mushaf. The research method used is a qualitative research method with the type of library research. The conclusion of this paper explains that there is a discrepancy and inconsistency in the writing of rasm and punctuation (dabt) of hamzah in the Indonesian Standard Mushaf with the rules of writing hamzah from the perspective of ad-Daniy and Abu Dawud. In the writing of rasm hamzah, seven words were found spread across ten places. As for the writing of punctuation (dabt) of hamzah, fifteen words were found spread across twenty places. This conclusion was obtained by analyzing the theory of writing hamzah in rasm 'Uthmani through qualitative data analysis, namely by analyzing the rules of writing hamzah in books and journals that are relevant to the science of rasm 'Uthmani, as well as diacritical studies (dabt) of classical and contemporary Al-Qur'an manuscripts.